The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/ma8125454
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Interfacial Studies of HfxTi1–xO2 High Permittivity Gate Insulators Deposited on Germanium Substrates

Abstract: In this research, the hafnium titanate oxide thin films, TixHf1–xO2, with titanium contents of x = 0, 0.25, 0.9, and 1 were deposited on germanium substrates by atomic layer deposition (ALD) at 300 °C. The approximate deposition rates of 0.2 Å and 0.17 Å per cycle were obtained for titanium oxide and hafnium oxide, respectively. X-ray Photoelectron Spectroscopy (XPS) indicates the formation of GeOx and germanate at the interface. X-ray diffraction (XRD) indicates that all the thin films remain amorphous for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The prompt SET and gradual RESET in the multilayered systems can explain the rejuvenation of CFs. Analogous to this design, several studies have suggested partial rupture and formation of CFs in multilayered NVBRS devices. ,− This design helps in making the device reproducible and technologically feasible. The log I –log V for the performing device follows a Ohmic and SCLC as shown in Figure S32a,b.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The prompt SET and gradual RESET in the multilayered systems can explain the rejuvenation of CFs. Analogous to this design, several studies have suggested partial rupture and formation of CFs in multilayered NVBRS devices. ,− This design helps in making the device reproducible and technologically feasible. The log I –log V for the performing device follows a Ohmic and SCLC as shown in Figure S32a,b.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, the incorporation of hafnium oxide into the TiO 2 layer increases the defect concentration and decreases the formation energy of V O , thus increasing the memory window and decreasing the operating voltage range, , which can directly be observed from the device performance. Herein, the metal oxide base layers not only ameliorate the interfacial anomalies by posing as interlayers but also are originally reservoirs of supplementary oxygen ions, thereby influencing the operating voltage of the device while preventing leakage of current and penetration of electrode materials. The distribution of operating voltage for nearly 25 devices is taken to test the reliability of the device (Figure S29c). The multibit storage levels are obtained by different LRS levels corresponding to the size of the filament obtained by controlling the CC (Figures S29d and S30a).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] The hydroxide peak also overlaps with the Ge 2 III O 3 and the peak at 532.5 eV is in accordance with Ge IV O 2 . 17 To this point, the Fe 6 Ge 5 characterisation uncovers a highly active OER catalyst consisting of a conductive Fe 6 Ge 5 core and an in situ formed amorphous shell. The stoichiometry of the newly formed shell is K x FeO 2 H y .…”
Section: 2184mentioning
confidence: 92%
“…S6b, ESI †). 17 For OER investigations of Fe 6 Ge 5 , we deposited 0.4 mg cm À2 on fluorine doped tin oxide (FTO) glass plates using a binder-free method (electrophoretic deposition (EPD), see ESI † for details and Fig. S7 and S8 for SEM/EDX data of the thin film).…”
mentioning
confidence: 99%
“…The horizontal red lines represent the conduction edges, and the horizontal blue lines represent the valence band edges. The right-hand y -axis also represents the redox potential of different chemical species involved in common photocatalytic reactions. , …”
Section: Introductionmentioning
confidence: 99%